2023
DOI: 10.1111/1541-4337.13160
|View full text |Cite
|
Sign up to set email alerts
|

The underlying mechanism of bacterial spore germination: An update review

Abstract: Bacterial spores are highly resilient and universally present on earth and can irreversibly enter the food chain to cause food spoilage or foodborne illness once revived to resume vegetative growth. Traditionally, extensive thermal processing has been employed to efficiently kill spores; however, the relatively high thermal load adversely affects food quality attributes. In recent years, the germination-inactivation strategy has been developed to mildly kill spores based on the circumstance that germination ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 242 publications
0
4
0
Order By: Relevance
“…The next set of experiments consisted of investigating germination at various concentrations of L-alanine in more detail. The pathways involved in endospore germination have been extensively studied in the past few years and summarised in detail by Lyu et al (Lyu et al 2023). Briefly, receptors located in the inner membrane or cortex receive signals from germinants, eventually triggering germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next set of experiments consisted of investigating germination at various concentrations of L-alanine in more detail. The pathways involved in endospore germination have been extensively studied in the past few years and summarised in detail by Lyu et al (Lyu et al 2023). Briefly, receptors located in the inner membrane or cortex receive signals from germinants, eventually triggering germination.…”
Section: Discussionmentioning
confidence: 99%
“…The 4CMC device was then used to study the germination of B. subtilis spores in more detail upon exposure to a concentration gradient (1 μM, 100 μM, 10 mM and 1 M) of L-alanine (Video 2). L-alanine has been studied extensively, but not using methods that give direct single spore level information about germination events (Lyu et al 2023). The relative frequency distributions of the spore germination time, showing what fraction of the analysed spores germinated within each 5-minute interval, are displayed in Figure 3A-D.…”
Section: Responsiveness Of B Subtilis Spores To Different Germinantsmentioning
confidence: 99%
“…To our knowledge, base excision repair is a major pathway for the removal of endogenous and exogenous DNA damage caused by environmental stress [41][42][43]. Additionally, the upregulation spore formation suggests that the gut microbiota is adapting to environmental stress [44,45]. The metabolic burden of HRP sows, particularly in amino acid and energy metabolism (as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the scientific literature have reported the enhanced susceptibility of germinating spores to inactivation [8][9][10][11]. Spore germination can be triggered by exposure to various molecules such as amino acids, sugars, and cell wall muropeptides, which can bind to receptors on the inner spore membrane [12,13].…”
Section: Introductionmentioning
confidence: 99%